Synthesis and Characterization of High‐Energy, High‐Power Spinel‐Layered Composite Cathode Materials for Lithium‐Ion Batteries. Issue 5 (20th November 2014) - Bhaskar, Aiswarya; Krueger, Steffen; Siozios, Vassilios; Li, Jie; Nowak, Sascha; Winter, Martin
<x xml:space="preserve">Abstract</x> Spinel‐layered composites, where a high‐voltage spinel is incorporated in a layered lithium‐rich (Li‐rich) cathode material with a nominal composition x{0.6Li2MnO3 · 0.4[LiCo0.333Mn0.333Ni0.333]O2} · (1 – x) Li[Ni0.5Mn1.5]O4 (x = 0, 0.3, 0.5, 0.7, 1) are synthesized via a hydroxide assisted coprecipitation route to generate high‐energy, high‐power cathode materials for Li‐ion batteries. X‐ray diffraction patterns and the cyclic voltammetry investigations confirm the presence of both the parent components in the composites. The electrochemical investigations performed within a wide potential window show an increased structural stability of the spinel component when incorporated into the composite environment. All the composite materials exhibit initial discharge capacities >200 mAh g–1. The compositions with x = 0.5 and 0.7 show excellent cycling stability among the investigated materials. Moreover, the first cycle Coulombic efficiency achieve a dramatic improvement with the incorporation of the spinel component. More notably, the composite materials with increased spinel component exhibit superior rate capability compared with the parent Li‐rich material especially together with the highest capacity retention for x = 0.5 composition, making this as the optimal high‐energy high‐power material. The mechanisms involved in the symbiotic relationship of the spinel and layered Li‐rich components in the above composites are discussed.